Drivers Of Development Inequality In North Sumatra: Economic Growth, Agglomeration, Human Development Index And Government Expenditure - Hakim, Sukma Hayati (Universitas Bengkulu, 2024)
Abstract Regional development disparities among cities in North Sumatra remain a crucial issue in regional economics, impacting uneven growth and societal welfare. This study analyzes urban development inequality in eight cities in North Sumatra from 2011 to 2023 using the Williamson Index (IW) and panel data regression analysis. The findings indicate that the average regional development inequality is moderate, with an IW value of 0.31, though significant disparities exist among cities. Medan exhibits the highest inequality (IW = 0.836) due to economic dominance and urbanization concentrated in trade and industry sectors, while Pematang Siantar records the lowest inequality (IW = 0.054) with more balanced development distribution. Simultaneously, economic growth, the Human Development Index (HDI), agglomeration, and local government capital expenditure significantly influence regional disparities. However, in a partial analysis, only HDI (p = 0.0092) and agglomeration (p = 0.000) are found to have a significant impact, whereas economic growth and government capital expenditure do not show a significant effect. These findings highlight that economic agglomeration is the most dominant factor exacerbating inequality, while an increase in HDI tends to widen disparities if development distribution remains uneven. Therefore, more effective policies are needed, such as redistribution of investment based on HDI, optimization of capital expenditure allocation for infrastructure in underdeveloped areas, and economic incentives to promote more balanced growth beyond Medan. Keywords: Regional Inequality, Economic Growth, Human Development Index, Agglomeration, Government Capital Expenditure Abstrak Kesenjangan pembangunan regional di antara kota-kota di Sumatera Utara tetap menjadi masalah penting dalam ekonomi regional, yang berdampak pada pertumbuhan yang tidak merata dan kesejahteraan masyarakat. Penelitian ini menganalisis ketimpangan pembangunan perkotaan di delapan kota di Sumatera Utara dari tahun 2011 hingga 2023 menggunakan Williamson Index (IW) dan analisis regresi data panel. Temuan menunjukkan bahwa rata-rata ketimpangan pembangunan daerah sedang, dengan nilai IW 0,31, meskipun ada kesenjangan yang signifikan antar kota. Medan menunjukkan ketimpangan tertinggi (IW = 0,836) karena dominasi ekonomi dan urbanisasi yang terkonsentrasi pada sektor perdagangan dan industri, sedangkan Pematang Siantar mencatat ketimpangan terendah (IW = 0,054) dengan distribusi pembangunan yang lebih seimbang. Secara bersamaan, pertumbuhan ekonomi, Indeks Pembangunan Manusia (IPM), aglomerasi, dan belanja modal pemerintah daerah secara signifikan mempengaruhi kesenjangan regional. Namun, dalam analisis parsial, hanya IPM (p = 0,0092) dan aglomerasi (p = 0,000) yang ditemukan memiliki dampak yang signifikan, sedangkan pertumbuhan ekonomi dan belanja modal pemerintah tidak menunjukkan efek yang signifikan. Temuan ini menyoroti bahwa aglomerasi ekonomi adalah faktor paling dominan yang memperburuk ketimpangan, sementara peningkatan IPM cenderung memperlebar kesenjangan jika distribusi pembangunan tetap tidak merata. Oleh karena itu, diperlukan kebijakan yang lebih efektif, seperti redistribusi investasi berbasis IPM, optimalisasi alokasi belanja modal untuk infrastruktur di daerah tertinggal, dan insentif ekonomi untuk mendorong pertumbuhan yang lebih seimbang di luar Medan. Kata Kunci: Ketimpangan Pembangunan, Pertumbuhan Ekonomi, Indeks Pembangunan Manusia, Aglomerasi, Belanja Modal Pemerintah